THE EFFECT OF DIFFERENT KIND OF CITRUS ON THE QUALITY OF JELAWAT FISH (Leptobarbus hoevenii) NANIURA - Christine Natalia Hutapea; Tjipto Leksono; N Ira Sari (Berkala Perikanan Terubuk, 2019)
This study aimed to know the effect of the using of different citrus on the quality of hoven's carp fish naniura and to determine the other kind of citrus to substitute the jungga (Citrus jambhiri) in naniura processing. The research method used was experimental composed as a non-factorial completely randomized design (CRD). The treatment conducted was the using of different kinds of citrus (jungga, lime, lemon) in the processing of naniura. The results showed that the different citrus used was significantly affecting the organoleptic values (appearance, odor, taste, and texture), pH, water holding capacity, total plate number of bacteria, and a total of lactic acid bacteria. The best treatment is the use of lime (Citrus aurantifolia) with the characteristics of the appearance yellow-orange color, quite bright, and not pale; the odor was not smelling fishy but smelling characteristically naniura; the taste was sour and spicy, and the texture was soft and not hard. Naniura used of lime has a pH value of 4.8, water holding capacity 53.2, total plate number 3.6 x 103 Cfu/g, and lactic acid bacteria 4.3 x 105 Cfu/g